Architects at the Mixing Desk: Workflows Cutting Across the Whole‐Life Process. (May 2017) - Sinclair, Dale
Abstract : Despite the collaborative, holistic approach discussed throughout this 2, most architects still remain rooted in the concept design stage.Dale Sinclair – Director of Technical Practice, Architecture at global engineering firm AECOM and a regular speaker on the future of the built environment industry – argues that several cultural shifts are needed. Not only should architects open themselves up to new building methods that allow them to digitally tweak simulations like a music producer at a mixing desk. They should also make broader use of digital technology to learn from their buildings' longer‐term outcomes, and feed this knowledge back into subsequent projects.